Acoustic emission in friction - Baranov, V. M. (Viktor Mikhailovich), 1935- (Tribology and interface engineering series ;, 2007)
Acoustic Emission in Friction is devoted to acoustic, mainly ultrasonic, emission that occurs in friction of machine components. Its crucial novelty is in systematizing the advances in its use for monitoring technical systems, especially in the important nuclear power industry. Written by four well-known experts from the main nuclear research university in Russia, this book covers the following areas: * All the sources of acoustic emission in friction. * The theory of acoustic emission. * The effects of surface conditions, load and velocity on acoustic emission. * The equipment for registration and monitoring of acoustic emission. * Unique data from acoustic emission control under various testing conditions in friction units of machinery for nuclear industry machinery. There is much emphasis on the comparatively new and rapidly developing tribology of nuclear power engineering. Although a substantial part of the experimental data relates to this specific field of engineering, the universality of the method is shown and its application is possible wherever the field inspection of friction units is necessary. * Calculation expressions describing main characteristics of AE registered in friction units * Describes new set-ups for studying the tribological behaviour of nuclear engineering materials * Presents the theory of the acoustic emission method in friction units.